Comparison of MAFLD and NAFLD diagnostic criteria in real world. (26th July 2020) - Lin, Su; Huang, Jiaofeng; Wang, Mingfang; Kumar, Rahul; Liu, Yuxiu; Liu, Shiying; Wu, Yinlian; Wang, Xiaozhong; Zhu, Yueyong
Abstract: Background and aims: Metabolic associated fatty liver disease (MAFLD) is a novel concept proposed in 2020, the utility of which has not been tested and validated in real world. We aimed to compare the characteristics of MAFLD and non‐alcoholic fatty liver disease (NAFLD). Methods: The data was retrieved from the third National Health and Nutrition Examination Surveys of the United States, which is an unbiased survey dataset and frequently used for the study of fatty liver disease. Results: A total of 13 083 cases with completed ultrasonography and laboratory data were identified from the NHANES III database. MAFLD was diagnosed in 4087/13 083 (31.24%) participants, while NAFLD in 4347/13 083 (33.23%) amongst the overall population and 4347/12 045 (36.09%) in patients without alcohol intake and other liver diseases. Compared with NAFLD, MAFLD patients were significantly older, had higher BMI level, higher proportions of metabolic comorbidities (diabetes, hypertension) and higher HOMA‐IR, lipid and liver enzymes. MAFLD patients with alcohol consumption were younger than those without, and more likely to be male. They had less metabolic disorder but higher liver enzymes. There were more cases with advance fibrosis in MAFLD patients with alcohol consumption. Conclusion: MAFLD definition is more practical for identifying patients with fatty liver disease with high risk of disease progression.